INCINERATION FOR MUNICIPAL SOLID WASTE TREATMENT - Yuliani, Manis (BPPT, 2016)
In order to reduce the accumulation of waste in landfill, incineration technology could becomes one of the solutions. In addition to reduce the volume of waste, the energy generated by incineration process can also be utilized. Plant Incineration consists of four categories process, namely pre-treatment process, combustion process, energy recovery process and flue gas treatment process (Air Pollution Control system). Pre-treatment process is used to increase the average calorific value of waste. Pre-treatment process depends on the type of incinerator used. Combustion process in an incinerator must accommodate the principles of 3 T (temperature, turbulence, time). Process conditions for the type of incinerator grate in accordance with the principle of 3 Tare the waste residence time in the grate less than 60 minutes, gas residence time more than 2 seconds and the gas temperature over 850 C. In the combustion process will produce heat carried by flue gas. The heat will flow into energy recovery process to be utilized. From energy recovery process, flue gas will enter into the APC system to reduce air pollution caused by combustion process.keywords : incinerator, waste, energy recovery